Diverse genetic causes of amenorrhea in an ethnically homogeneous cohort and an evolving approach to diagnosis - Bakhshalizadeh,S; Afkhami,F; Bell,KM; Robevska,G; van,den Bergen J; Cronin,S; Jaillard,S; Ayers,KL; Kumar,P; Siebold,C; Xiao,Z; Tate,EW; et al. (Molecular and Cellular Endocrinology, 2024)
RESEARCH QUESTION: Premature ovarian insufficiency (POI) is characterised by amenorrhea associated with elevated follicle stimulating hormone (FSH) under the age of 40 years and affects 1-3.7% women. Genetic factors explain 20-30% of POI cases, but most causes remain unknown despite genomic advancements. DESIGN: We used whole exome sequencing (WES) in four Iranian families, validated variants via Sanger sequencing, and conducted the Acyl-cLIP assay to measure HHAT enzyme activity. RESULTS: Despite ethnic homogeneity, WES revealed diverse genetic causes, including a novel homozygous nonsense variant in SYCP2L, impacting synaptonemal complex (SC) assembly, in the first family. Interestingly, the second family had two independent causes for amenorrhea - the mother had POI due to a novel homozygous loss-of-function variant in FANCM (required for chromosomal stability) and her daughter had primary amenorrhea due to a novel homozygous GNRHR (required for gonadotropic signalling) frameshift variant. WES analysis also provided cytogenetic insights. WES revealed one individual was in fact 46, XY and had a novel homozygous missense variant of uncertain significance in HHAT, potentially responsible for complete sex reversal although functional assays did not support impaired HHAT activity. In the remaining individual, WES indicated likely mosaic Turners with the majority of X chromosome variants having an allelic balance of ∼85% or ∼15%. Microarray validated the individual had 90% 45,XO. CONCLUSIONS: This study demonstrates the diverse causes of amenorrhea in a small, isolated ethnic cohort highlighting how a genetic cause in one individual may not clarify familial cases. We propose that, in time, genomic sequencing may become a single universal test required for the diagnosis of infertility conditions such as POI.